METODE PROBLEM SOLVING DALAM UPAYA PENGENDALIAN SOSIAL PADA KASUS TINDAK KEJAHATAN : STUDI KASUS PADA BHABINKAMTIBMAS POLSEK PEKANBARU KOTA - Azim , Kabiyrul; Rinaldi, Kasmanto (Gapenas Publisher, 2024)
In an effort to control social behaviour, the Indonesian National Police implemented the concept of community policing (Polmas). The police then formed the Binmas or Bina Masyarakat unit as the spearhead of community service. Pekanbaru Kota Police Station as Harkamtibmas Police Station is not equipped with Criminal Investigation unit. The purpose of this research is to examine the implementation of problem solving in dealing with the phenomenon of crime, as well as the correlation between problem solving policies and social control efforts. The research was conducted using qualitative methods, with data collection techniques by interview and documentation. From the results of interviews with informants, it can be concluded that the presence of problem solving is a form of alternative case handling other than procedural law, where this policy prioritises the principle of consensus so that cases can be resolved through mediation between parties. In its implementation, apart from Bhabinkamtibmas, the Kelurahan government also participated in the mediation process between problem parties, represented by RT/RW